(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
Ginger marketers in Nigeria operate in a subsistence economy with the use of local technology. The subsistence economy resulted in the use of local knowledge with little commercialization. Therefore, improving ginger marketing to commercial form is faced with post-production challenges ranging from local processing techniques and inadequate credit, which often results in low and poor ginger marketing. The study improved our understanding of all the complexities affecting the microcredit use and the performance of ginger marketers in South East Nigeria. This study evaluated the determinants of microcredit use among ginger marketers in Southeast, Nigeria. A multi-stage sampling procedure was used in selecting one hundred and eighty (180) respondents for the study. A well-structured questionnaire was used in collecting data from the respondents and the data collected were analyzed using frequency distribution and Heckman selectivity model. The second stage of the selectivity model was used to determine the level of the determinants of microcredit use among ginger marketers. The result shows that majority of the marketers were females and are married, they are still in their active age of 31-50 years which had the highest representatives of 64.17%. The result of the estimation of the determinants of microcredit use among ginger marketers indicates that a 1.0% decrease in the distance to the source of microcredit, increase microcredit use by 0.31% for those already marketing ginger and 0.04% for participation, and 0.35% for all marketers. An increase in educational level, led to a rise in microcredit use for those who are already marketing, for participation and all marketers of ginger respectively. It is therefore recommended that those marketing ginger should acquire higher education, since the high literacy level is essential for the use of microcredit in ginger marketing.